Pengaruh Stres Kerja, Motivasi Kerja, Kepemimpinan, Konflik Kerja, Dan Kompensasi Terhadap Kepuasan Kerja Karyawan (Studi Pada Pt. Bank Bukopin,Tbk. Cabang Solo) - Kuncahyo, Arif; , Zulfa Irawati, S.E., M.Si (2015)
This study attempts to know how big the influence of job stress, motivation work , leadership , conflict work , and compensation to satisfaction work employees in PT. Bank Bukopin.Tbk. Branch of Solo. This research will prove a hypothesis that job stress , motivation of work , leadership , labor conflict , and compensation in partial influential significantly to the satisfaction of employees work in a bank. This study using primary and secondary data. Sample in this research using 83 of respondents taken from an employee at PT. Bank Bukopin. Tbk. Branch of Solo. The sample collection technique uses the technique purposive of sampling. The method of analysis research conducted it uses the linear regression multiple, while using test the hypothesis T test. The method of analysis research conducted it uses the linear regression multiple, While using test hipotesisnya T test , F test, And coefficients determination (R2). The result of investigation at data give this conclusion job stress, Motivation work, leadership, conflict work, and compensation affect satisfaction working with the regression equation is as follows Y = 0,196 + 0,129 X1 + 0,237 X2 + 0,280 X3 + 0,174 X4 + 0,176 X5. This research give this conclusion job stress, motivation work, leadership, conflict work, and compensation in partial have a positive influence and significant impact on satisfaction work in PT. Bank Bukopin. Tbk. Branch of Solo. In addition together variable job stress, motivation work , leadership , conflict work , and compensation having significant impact on satisfaction work in PT. Bank Bukopin.Tbk. Branch of Solo. Variable job stress, motivation work, leadership, work conflict, and compensation influential 50 percent against satisfaction employees work.